Safety of intravenous thrombolysis for ischemic stroke in patients treated with warfarin. Issue 2 (4th September 2013) - Mazya, Michael V.; Lees, Kennedy R.; Markus, Romesh; Roine, Risto O.; Seet, Raymond C. S.; Wahlgren, Nils; Ahmed, Niaz; ,
<x xml:space="preserve">Abstract</x> Objective Controversy surrounds the safety of intravenous (IV) tissue plasminogen activator (tPA) in ischemic stroke patients treated with warfarin. The European tPA license precludes its use in anticoagulated patients altogether. American guidelines accept IV tPA use with an international normalized ratio (INR) ≤ 1.7. The influence of warfarin on symptomatic intracerebral hemorrhage (SICH), arterial recanalization, and long‐term functional outcome in stroke thrombolysis remains unclear. Methods We analyzed data from 45, 074 patients treated with IV tPA enrolled in the Safe Implementation of Thrombolysis in Stroke (SITS) International Stroke Thrombolysis Register. A total of 768 patients had baseline warfarin treatment with INR ≤ 1.7. Outcome measures were SICH, arterial recanalization, mortality, and functional independence at 3 months. Results Patients on warfarin with INR ≤ 1.7 were older, had more comorbidities, and had more severe strokes compared to patients without warfarin. There were no significant differences between patients with and without warfarin in SICH rates (adjusted odds ratio [aOR] = 1.23, 95% confidence interval [CI] = 0.72–2.11 per SITS‐MOST; aOR = 1.26, 95% CI = 0.82–1.70 per European Cooperative Acute Stroke Study II) after adjustment for age, stroke severity, and comorbidities. Neither did warfarin independently influence mortality (aOR = 1.05, 95% CI = 0.83–1.35) or functional independence at 3 months (aOR = 1.01, 95% CI = 0.81–1.24). Arterial recanalization by computed tomography/magnetic resonance angiography trended higher in warfarin patients (62% [37 of 59] vs 55% [776/1, 475], p = 0.066). Recanalization approximated by disappearance at 22 to 36 hours of a baseline hyperdense middle cerebral artery sign was increased (63% [124 of 196] vs 55% [3, 901 of 7, 099], p = 0.022). Interpretation Warfarin treatment with INR ≤ 1.7 did not increase the risk for SICH or death, and had no impact on long‐term functional outcome in patients treated with IV tPA for acute ischemic stroke. Ann Neurol 2013;74:266–274